PERSEPSI MASYARAKAT PERKOTAAN TERHADAP LAYANAN SMART CITY: MODEL UTAUT2 - Harsono, Subambang; Rinanda, Teja; Tarigan, Imanuel (Jurnal Manajemen dan Bisnis, 2023)
In this study, we look at technology readiness related to performance expectancy and effort expectancy from UTAUT2 to analyze urban community perceptions of smart city services. Data is collected using a survey questionnaire. We use Partial Least Square Structural Equation Modeling (PLS-SEM) analysis. The questionnaire consists of 16 items on the Technology Readiness Index 2.0 scale to measure technological readiness and the UTAUT2 scale which has 29 items. The research of the study shows that optimism has a positive effect on performance expectancy and effort expectancy in using smart services. This means that respondents believe and have a sense of optimism that smart city service technology will be understood and used. Effort expectancy, facilitation conditions, and hedonic motivation have a positive effect on the intention to use smart services. It can be said that although some users are anxious about the new technology, it will not have an impact on the usability and ease of use of smart service technology.